Polymorphism of protein genes associated with endothelial function in patients with infective endocarditis - A. V. Ponasenko; A. V. Tsepokina; A. G. Kutixin; Yu. A. Kudryavtseva (Российский кардиологический журнал)
Aim. To study relationship between the polymorphism of five polymorphic sites of EDN1, SELE, SELP, SELPLG genes with the risk of infectious endocarditis (IE) and the connection of genotypes of studied sites with concentration of the corresponding proteins in the blood.Material and methods. The study included 208 patients with IE and 300 healthy donors. Genotyping was performed on 6 polymorphic sites of 4 genes by real-time PCR. The levels of endothelin-1, sE-selectin, sP-selectin were determined by the ELISA technique. Results. We determined that the T allele (G/T genotype) of rs5370 polymorphic site of EDN1 gene have a risk effect on IE in the superdominant mode of inheritance (OR=1,58, 95% CI=1,05-2,35, p=0,027). At the same time, the association between levels of endothelin-1, sE and sP selectins and carriage of the variable genotypes of the corresponding genes was not found. We noted that serum concentrations of biologically active endothelial proteins differ between patients with IE and healthy individuals. Conclusion. The study confirms the presence of endothelial dysfunction markers in the blood of patients with IE. It shows the association between rs5370 site of EDN1 gene and an increased risk of IE in heterozygous carriers of the minor T allele. However, additional research is needed to confirm these observations and to get detailed description of how gene variability determines underlying risk for IE.